Insect Management for Tomatoes, Peppers, and Eggplant - Susan E. Webb; Philip A. Stansly; David J. Schuster; Joe E. Funderburk (EDIS, 2005)
Pest management should be based on the proper identification of pests and knowledge of their biology. The major pests of tomatoes, peppers, and eggplant in Florida and guidelines for their management are described in this document. Some insects may be more important in some areas of the state than others. Scouting guidelines and action thresholds for tomatoes are from the Florida Tomato Scouting Guide, SP 22, 2nd edition. This document is ENY-461, one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2001. Revised: August 2005.